(untitled) (aSSIST Business Review, 2025)
This study explores how latecomer firms—often disadvantaged in brand recognition and resource endowment—can reshape market dynamics through strategic execution. To this end, it adopts the SER-M model, which comprises four core components: Subject, Environment, Resource, and Mechanism. The model is applied to analyze Apple’s entry into the smartphone market and the execution of its product strategies. Despite being a late entrant, Apple outperformed market leaders by establishing a unique strategic execution structure. It aligned its emotionally driven strategic philosophy with a reinterpreted market paradigm, integrated its design, technology, and brand assets, and implemented a robust execution mechanism through cross-functional alignment and KPI-driven management routines. Steve Jobs’ leadership was central to embedding the strategy into the organizational fabric, ensuring strategic coherence across all functions. Through a comparative analysis with Samsung and Nokia, the study highlights that the key determinant of strategic success lies not in planning but in the structural alignment of execution. It demonstrates the practical applicability of the SER-M model in diagnosing execution gaps and designing implementable strategies. The findings provide both theoretical insights and managerial implications for latecomer firms and organizations struggling with strategy-to-execution translation.